Assessment of Recycled Plastic Performance in The City of Zawia Libya - Abosbaia, Alhadi A; Alkrbash, Abdulbaset S; Elsheikhi, Salah A.; Alkbir, Munir F.; M A Elfaghi, Abdulhafid (International Journal of Integrated Engineering, 2022)
Plastic particles and other plastic pollutants exist in our environment and in the food chain and threaten human health. Inappropriate handling and disposal of plastic waste is a global problem and is still not resolved in many countries. When recycling companies need to deal with complex plastic, the problem becomes even more serious, which can prevent their recycling initiatives. The main purpose of this research is to determine whether recycled products can be used as post-consumer materials in various recycling ratios to produce new products without reducing quality. In the study, 0 percent, 20%, 50%, 70%, and 100 percent regrind ratios were used. Reduction, hardness, and solid density are the qualities studied. The results show that the properties did not change significantly.